Human microbiomes in cancer development and therapy - Chenglai Xia; Jiyan Su; Can Liu; Zhikai Mai; Shuanghong Yin; Chuansheng Yang; Liwu Fu (MedComm)
Abstract Colonies formed by bacteria, archaea, fungi, and viral groups and their genomes, metabolites, and expressed proteins constitute complex human microbiomes. An increasing evidences showed that carcinogenesis and disease progression were link to microbiomes. Different organ sources, their microbial species, and their metabolites are different; the mechanisms of carcinogenic or procancerous are also different. Here, we summarize how microbiomes contribute to carcinogenesis and disease progression in cancers of the skin, mouth, esophagus, lung, gastrointestinal, genital, blood, and lymph malignancy. We also insight into the molecular mechanisms of triggering, promoting, or inhibiting carcinogenesis and disease progress induced by microbiomes or/and their secretions of bioactive metabolites. And then, the strategies of application of microorganisms in cancer treatment were discussed in detail. However, the mechanisms by which human microbiomes function are still poorly understood. The bidirectional interactions between microbiotas and endocrine systems need to be clarified. Probiotics and prebiotics are believed to benefit human health via a variety of mechanisms, in particular, in tumor inhibition. It is largely unknown how microbial agents cause cancer or how cancer progresses. We expect this review may open new perspectives on possible therapeutic approaches of patients with cancer.